2015
DOI: 10.1002/star.201500109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freeze‐thawing treatment on the microstructure and thermal properties of non‐waxy corn starch granule

Abstract: In the present study, non-waxy corn starch was processed by different freeze-thawing temperatures and cycles. The effects of freeze-thawing treatment on the surface structure, granules particle size, Maltese crosses, crystalline, and thermal properties of non-waxy corn starch were investigated. The number of pores on the surface of starch granules increased with freeze-thawing cycles. The granule size, crystalline intensity and degree, gelatinization temperatures, and enthalpy values of corn starch decreased w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 14 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…The internal and external molten ice crystals may result in pores on the surface of starch granules. The morphology and melting of ice crystals create a certain microscopic mechanical force on the starch granules, expanding the internal channel molecules of starch so that more soluble components are dissolved, water is redistributed, and more dents appear in the pores and starch granules (Yu, Zhang, Li, Yan, Gong, Liu, et al, 2015).…”
Section: Bulk Densities and Porositymentioning
confidence: 99%
“…The internal and external molten ice crystals may result in pores on the surface of starch granules. The morphology and melting of ice crystals create a certain microscopic mechanical force on the starch granules, expanding the internal channel molecules of starch so that more soluble components are dissolved, water is redistributed, and more dents appear in the pores and starch granules (Yu, Zhang, Li, Yan, Gong, Liu, et al, 2015).…”
Section: Bulk Densities and Porositymentioning
confidence: 99%
“…Cracks on the granule surfaces were also observed by Yu et al. [ 24 ] They suggested that the formation of small ice crystals caused the outer layers of the granules to peel. Tao et al.…”
Section: Resultsmentioning
confidence: 66%
“…The X-ray pattern of native revealed A-type starch pattern with two singles at 15° and 23°, and a double at 17° and 18° (2θ), and the freeze-thawed starch still exhibited A-type ( Figure 2), which was consistent with the result of Yu et al, who found that the crystal type of non-waxy corn starch still appeared A-type after freezethaw treatment. [10] However, the crystallinity of the native maize starch (19.93%) was significantly (P < .05) higher than that of the freeze-thaw cycle treated maize starch (15.21%-18.56%), and the crystallinity decreased non-significantly at freezing −80 °C with the freeze-thawing cycle times increased ( Table 1). The result was similar to the studies of Yu et al, who found that the crystallinity of non-waxy corn starch decreased after freeze-thaw treatment, [10] while the crystallinity of freezethaw of moistened potato starch granules was found to increase after freeze-thaw treatment.…”
Section: X-ray Diffraction Pattern Analysismentioning
confidence: 93%
“…[10] However, the crystallinity of the native maize starch (19.93%) was significantly (P < .05) higher than that of the freeze-thaw cycle treated maize starch (15.21%-18.56%), and the crystallinity decreased non-significantly at freezing −80 °C with the freeze-thawing cycle times increased ( Table 1). The result was similar to the studies of Yu et al, who found that the crystallinity of non-waxy corn starch decreased after freeze-thaw treatment, [10] while the crystallinity of freezethaw of moistened potato starch granules was found to increase after freeze-thaw treatment. [7] That might be due to the different conditions in freezing and thawing treatment and the different types of samples.…”
Section: X-ray Diffraction Pattern Analysismentioning
confidence: 93%
See 1 more Smart Citation